High-throughput DNA sequencing of museum specimens sheds light on the long-missing species of the Bokermannohyla claresignata group (Anura: Hylidae: Cophomantini) - Lyra, Mariana L [UNESP]; Lourenço, Ana Carolina C; Pinheiro, Paulo D.P.; Pezzuti, Tiago L.; Baêta, Délio [UNESP]; Barlow, Axel; Hofreiter, Michael; Pombal, José P; Haddad, Célio F.B. [UNESP]; Faivovich, Julián (Oxford University Press (OUP), 2020)
The two species of the Bokermannohyla claresignata species group (Anura: Hylidae) have not been collected for the last four decades. It is the only species group of the hyline tribe Cophomantini that has not yet been analysed genetically. Its phylogenetic position is thus uncertain, and it has a combination of adult and larval character states that make this group a crucial missing piece that hinders our understanding of Cophomantini phylogenetics and character evolution. We obtained DNA sequences from a museum larval specimen of Bok. claresignata, using specialized extraction methods and high-throughput DNA sequencing, and combined the molecular phylogenetic results with available phenotypic information to provide new insights into the taxonomy and phylogenetic relationships of its species group. Our phylogenetic results place Bok. claresignata as sister to the Boana pulchella group, supporting its inclusion in Boana, together with Bokermannohyla clepsydra. In light of this new finding, we recognize a newly defined Boana claresignata group to accommodate these species, thus resolving both the polyphyly of Bokermannohyla and the paraphyly of Boana. Considering the phylogenetic relationships of the Boana claresignata group, we also discuss the evolution of suctorial tadpoles and mature oocyte/egg pigmentation in Cophomantini.
Keywords: archival DNA; Boana pulchella group; Hylinae; Museum; Phylogenetics; Taxonomy